Impaired Immune Response to Primary but Not to Booster Vaccination Against Hepatitis B in Older Adults - Weinberger, Birgit; Haks, Mariëlle C.; de Paus, Roelof A.; Ottenhoff, Tom H. M.; Bauer, Tanja; Grubeck-Loebenstein, Beatrix (Frontiers in Immunology, 2018)
Many current vaccines are less immunogenic and less effective in elderly compared to younger adults due to age-related changes of the immune system. Most vaccines utilized in the elderly contain antigens, which the target population has had previous contact with due to previous vaccination or infection. Therefore, most studies investigating vaccine-induced immune responses in the elderly do not analyze responses to neo-antigens but rather booster responses. However, age-related differences in the immune response could differentially affect primary versus recall responses. We therefore investigated the impact of age on primary and recall antibody responses following hepatitis B vaccination in young and older adults. Focused gene expression profiling was performed before and 1 day after the vaccination in order to identify gene signatures predicting antibody responses. Young (20–40 years; n = 24) and elderly (>60 years; n = 17) healthy volunteers received either a primary series (no prior vaccination) or a single booster shot (documented primary vaccination more than 10 years ago). Antibody titers were determined at days 0, 7, and 28, as well as 6 months after the vaccination. After primary vaccination, antibody responses were lower and delayed in the elderly compared to young adults. Non-responders after the three-dose primary series were only observed in the elderly group. Maximum antibody concentrations after booster vaccination were similar in both age groups. Focused gene expression profiling identified 29 transcripts that correlated with age at baseline and clustered in a network centered around type I interferons and pro-inflammatory cytokines. In addition, smaller 8- and 6-gene signatures were identified at baseline that associated with vaccine responsiveness during primary and booster vaccination, respectively. When evaluating the kinetic changes in gene expression profiles before and after primary vaccination, a 33-gene signature, dominated by IFN-signaling, pro-inflammatory cytokines, inflammasome components, and immune cell subset markers, was uncovered that was associated with vaccine responsiveness. By contrast, no such transcripts were identified during booster vaccination. Our results document that primary differs from booster vaccination in old age, in regard to antibody responses as well as at the level of gene signatures. Clinical Trial Registration www.clinicaltrialsregister.eu, this trial was registered at the EU Clinical Trial Register (EU-CTR) with the EUDRACT-Nr. 2013-002589-38.